Total Contact Casting vs Removable Cast Walker for 12-Week Healing of Neuropathic Plantar Diabetic Foot Ulcers: A Pragmatic Randomized Trial - Ayşe Demir Daysan; Mehmet Kaya Jason; Asnafi Elif Yılmaz (Indonesian Science Media, 2025)
Background: Diabetes-related foot ulceration remains a major clinical and health-system burden in outpatient care, with high risks of infection and amputation. Yet, evidence directly comparing non-removable total contact casts (TCC) versus removable cast walkers (RCW) on a uniform 12-week healing endpoint in routine clinics is limited. Purpose: This study compared the effect of TCC versus RCW on complete 12-week ulcer healing among adults with neuropathic plantar diabetic foot ulcers in outpatient care. Methods: In a pragmatic randomised controlled trial at Ankara City Hospital, Türkiye (2 January–30 March 2025), we enrolled 172 adults with neuropathic plantar ulcers (Wagner 1–2) meeting perfusion criteria; key exclusions were critical ischaemia and osteomyelitis. The intervention was a non-removable TCC versus RCW with standard wound care. The primary outcome was complete epithelialisation by 12 weeks, adjudicated blindly at two visits ≥2 weeks apart. Log-binomial (or Poisson-robust) models estimated risk ratios (RRs) with 95% CIs, adjusting for prespecified covariates; longitudinal percentage-area reduction and adherence-adjusted sensitivities were prespecified. Results: Among 172 participants (mean age ≈60 years; comorbidities common), 65/86 (75.6%) healed by 12 weeks with TCC versus 46/86 (53.5%) with RCW (RR 1.41, 95% CI 1.12–1.78). TCC also showed greater percentage-area reduction at 1, 2, and 3 months, consistent with a steeper healing trajectory; device-related adverse events were slightly higher with TCC, while infections requiring systemic antibiotics were similar. Findings were consistent in intention-to-treat and adherence-adjusted analyses, indicating robustness. Conclusion: TCC accelerated healing and increased 12-week ulcer closure versus RCW in routine outpatient care. Results support prioritising non-removable offloading where feasible and motivate multicentre evaluations of durability, safety, cost-effectiveness, and equitable implementation.